Assessment of disease activity of inflammatory bowel disease using positron emission tomography / magnetic resonance imaging and keratin 7 -analysis - Tenhami, Mervi (fi=Turun yliopisto|en=University of Turku|, 2024)
The clinical course of inflammatory bowel disease (IBD) is characterized by relapses and spontaneous or drug-induced remissions, but it cannot be predicted by currently known parameters. The priority of this thesis was to improve the accuracy of IBD diagnostics and to find methods in evaluating the course and the prognosis of IBD to facilitate individualized medication and to improve the outcome of the disease. Positron emission tomography and magnetic resonance imaging (PET/MRI) is a hybrid imaging modality in which MRI provides high spatial resolution and soft tissue contrast while PET using fluorodeoxyglucose (18F-FDG) detects metabolic activity related to inflammation. We compared the data of PET/MRI of altogether ten ulcerative colitis (UC) and Crohn’s disease (CD) patients to intestinal histological samples to find out the ability of PET/MRI to detect and grade the inflammation activity of bowel wall. The analysis showed that the glucose uptake in bowel wall had significant association to inflammation activity. Also, the standardized uptake values from areas of severe inflammation activity emerged significantly from the background. Consequently, 18F-FDG-PET/MRI is a promising method to detect especially severe inflammatory lesions non-invasively. The second aim was to investigate the expression of keratin 7 (K7) in IBD affected intestinal epithelial cells, and to evaluate its potential as prognostic biomarker of IBD. The study showed that K7 was expressed in the colonic epithelium of patients suffering from UC and CD, but not in healthy colon. The expression of K7 was the most pronounced in drug-resistant colitis. The analyses suggested also that K7 expression varies based on the anatomical location in colon. To evaluate the prognostic value of K7, the state of 16 patients was followed for three years. As a result, the severity of the disease during the following three years was not related to expression of K7 at the time of enrollment. Consequently, K7 could be used as a specific diagnostic marker for severe IBD, indicating especially disease with poor drug response and major pathological changes in epithelium.

Tulehduksellisten suolistosairauksien aktiivisuuden arviointi yhdistettyä positroniemissiotomografia / magneettiresonanssikuvausta ja keratiini 7-määritystä käyttäen Tulehduksellisten suolistosairauksien (IBD) taudinkulku on vaihteleva. Käytössä olevilla menetelmillä ei pystytä ennustamaan remissiovaiheen kestoa eikä tulevia relapseja. Tutkimuksen tavoitteena oli parantaa IBD:n diagnostiikkaa ja löytää taudin kulun ennustamiseen uusia menetelmiä, joiden avulla pystyttäisiin suunnittelemaan potilaan hoitoa yksilöllisemmin ja parantamaan taudin kulun ennustetta. Yhdistetty positroniemissiotomografia/magneettiresonanssikuvaus (PET/MRI) on hybridimenetelmä, jossa yhdistyvät MRI:n hyvä resoluutio ja pehmytkudoskontrasti, sekä PET-kuvauksen tuottama tieto kudoksen aineenvaihdunnasta. Tutkimuksessa selvitettiin PET/MRI:n soveltuvuutta IBD-muutosten havaitsemiseen suolen seinämässä sekä haavaista paksusuolitulehdusta (UC) että Crohnin tautia (CD) sairastavilla potilailla. Lisäksi tutkimuksessa verrattiin PET/MRI-tutkimuksen antamaa merkkiainekertymää ja suoliston histologisten näytteiden tulehdusaktiivisuutta toisiinsa. Tuloksista havaittiin, että suoliston seinämän glukoosikertymällä ja seinämän tulehdusaktiivisuudella on merkitsevä yhteys, ja että 18F-FDGPET/ MRI:llä pystytään havaitsemaan erityisesti suolen vaikeat tulehdusmuutokset, jotka erottuvat selkeästi normaalista kudoksesta. Tutkimuksen toisena tavoitteena oli tutkia, ilmeneekö keratiini 7:ää (K7) IBDpotilaiden suoliston epiteelisoluissa, ja tutkia sen ennusteellista merkitystä IBD:n vaikeusasteen arvioinnissa. Tutkimus osoitti, että K7:ää ilmenee sekä UC että CD potilaiden paksusuolen epiteelissä. K7:n ilmentyminen oli suurinta lääkeresistentissä paksusuolitulehduksessa. Tutkimus antoi myös viitteitä siitä, että suolen anatominen kohta vaikuttaa K7:n ilmentymiseen. K7:n ennusteellista arvoa tutkittiin seuraamalla 16 potilaan taudinkulkua kolmen vuoden ajan, jolloin K7:n ilmentymisen perusteella ei kuitenkaan voitu ennustaa taudin vaikeusastetta. Tuloksista voidaan päätellä, että K7:ää voidaan käyttää erityisesti vaikean IBD:n merkkiaineena.